Akuntabilitas BPJS Kesehatan Cabang Utama Yogyakarta Dalam Penanganan Klaim Asuransi Program Jaminan Kesehatan Nasional Januari – April 2014 - Eko Subardi; Suranto Suranto (Universitas Muhammadiyah Yogyakarta, 2014)
Healthcare and Social Security Agency (BPJS) is a government program, that started on January 1, 2014. at the EarlyImplementation is not yet completed. and has shor tcomings, among others payment of claims insurance JKN toGovernment’s Partner hospitals (BPJS). The aims of this research was to describe Healthcare and Social SecurityAgency (BPJS) accountability in claims insurance handling and factors that influence, This study used descriptive andqualitative data, While the research analysis using the da ta analysis process based on the result of in depth interviewand documents.. the result showed that accountability in claims insurance handling generally the result has beenaccountable (80,5 %) although several indicators to measure showed any discrepancy / not accountable. whenmeasured with indicator refers to a predetermined scheduler that is not accountable. The presence indicator adher-ence to rules and procedures have not been fully accountable. while ability indicator for do performance evaluationand Transparency Indicator in decision-making and to implement effecti veness and cost-eff iciency perf ormance of itsduties has been accountable. Then, to determine the factor s that the effect of accountability in claims insurancehandling used a variable factor of service rules, factor of bureaucratic apparatus and factors of priority interests andservice users. Application and implementation of the third factor have relevance and has a causal impact that influ-ence the Healthcare and Social Security Agency (BPJS) in claims insurance handling.